The War in Ukraine: Global Perspectives-Latin America - Carlos Sainz-Borgo, Juan (Juniata Voices, 2024)
The Baker Institute International Symposium: The War in Ukraine, October 22, 2022. Faced with the great cultural and political diversity that exists in Latin America, Juan Carlos Sainz-Borgo identifies a wide range of political reactions to Russia’s invasion of Ukraine. Countries such as Chile, Colombia, the Dominican Republic, and Peru have clearly condemned the invasion. Brazil and Mexico have voted against the invasion while projecting an image of neutrality. El Salvador has also maintained neutrality but supports Russia’s positions. Finally, Bolivia, Cubs, Nicaragua, and Venezuela have supported Russia’s position and criticized the United States and NATO. The different opinions on the invasion reflect the political diversity within Latin America.